Determination of level of self‐reported adherence of antihypertensive drug(s) and its associated factors among patient with hypertension at a tertiary care center. Issue 11 (27th October 2022) - Bhusal, Laxman; Deep Pathak, Bishnu; Dhakal, Bishal; Simkhada, Nabin; Sharma, Neeraj; Upadhaya Remi, Binit; Adhikari, Sushil; Oli, Prakash Raj; Neupane, Shashank; Limbu, Binod; Shrestha, Dhan Bahadur
Abstract: The study aimed to determine the level of self‐reported adherence to antihypertensive drug(s) and its associated factors among patient with hypertension at a tertiary care center. The authors performed hospital based observational cross‐sectional study using semi‐structured questionnaires, WHO STEP tool and Hill and Bone high blood pressure compliance scale from December 1, 2021 to February 28, 2022. Descriptive statistics, Chi‐square/Fisher's exact test and non‐parametric tests were used for statistical analysis. Among 150 cases included in the study, majority (94, 62.67%) had good adherence based on Hill and Bone high blood pressure compliance scale with adherence level labelled as "good adherence" (score 3) and "not good adherence" (score < 3). The adherence to drug therapy was significantly better in females compared to males (50 [71.43%] vs. 44 [55.00%], p = .038). Among the factors related to hypertension and anti‐hypertensive therapy, people with higher body mass index (ρ = ‐.324, n = 56, p = .015) and taking three or more pills (6, 1.71%, p = .017) had lower adherence to therapy. Likewise, forgetfulness (30, 53.57%), ineffective counseling (7, 12.50%), and missed follow‐up (13, 23.21%) were the factors associated with lower adherence to anti‐hypertensive therapy. This study finds good adherence among the patients taking anti‐hypertensive medications. However, with the improved education, lesser number of pills and physical fitness help to adhere with the anti‐hypertensive therapy.